PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP KESEJAHTERAAN MASYARAKAT PADA DESA KUREKSARI KAPUBATEN SIDOARJO DI PROVINSI JAWA TIMUR - Soesilowati Soema Atmadja (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
In this era of rapid globalization, the management of the area's financesgreatly affects the development of the area to determine the level of financialachievement of the area. Therefore, the management of regional finance should be doneeconomically efficiently and effectively or meet value for money as well astransparency, accountability, fairness and community participation in order toencourage economic growth that can further reduce the amount of budgeting andreduce the level of poverty. This research is intended to allow other villages to knowthat there is a simple stimulus that can be developed between the regional financial selfreliance ratio (X1), and the ratio of effectiveness PAD (X2) to community Welfare (Y) inSidoarjo. The high value of the ratio is not necessarily determining the prosperity of thecommunity so the opposite low ratio value is not necessarily determine the low welfareof society. This research uses a quantitative descriptive approach, which is a researchthat is related to hypothesis testing with analytic tools for the method of collectingobservation data, interviews and documentation. The test equipment used was a doubleregression analysis technique with Windows SPSS 22. Thus obtained the value of thevariable regression coefficient of the financial self-reliance area 0.452, variable ratio ofeffectiveness pad to 0.434. And the F test value of Fcalculate > Ftabel (3.509 > 3.20)with a significant rate of 0.015 < 0.05 which means the regional financial self-relianceratio variable and PAD's effectiveness ratio simultaneously affects the welfare of thecommunity. T-test result of regional financial independence ratio of Thitung > This(3.465 > 2.011) has a significant value of 0.014 < 0.05, and PAD effectiveness ratio ofThitung > This (3.959 > 2.011) has a significant value of 0.022 < 0.05, which meansthe variable ratio of regional financial independence and the ratio of effectiveness ofthe pad affects community welfare partially